Rett syndrome in childhood: the clinical characteristics - E S Herini; Irawan Mangunatmadja; Purboyo Solek; Hardiono D Pusponegoro (Paediatrica Indonesiana, 2004)
The prevalence rate of RS in various coun-tries is from 1:10,000 to 1:23,000 female livebirths. RS is most often misdiagnosed as autism,cerebral palsy, or non-specific developmental de-lay. While many health professionals may not befamiliar with RS, it is a relatively frequent cause ofneurological dysfunction in females. There are nobiological markers for this disease, the diagno-sis is established by history taking and clinical find-ings. We reported two patients, both girls, with RS.